Hubungan Strategi Koping dengan Tingkat Stres Mahasiswa Poltekkes Kemenkes Riau yang Menyusun Skripsi - Usraleli Usraleli; Melly Melly; Roza Deliana (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Scientific paper was a research report written and compiled using scientific principles by undergraduate students as one of the requirements for obtaining his degree. The problems faced by the students of Poltekkes Kemenkes Riau during the preparation of scientific paper such as difficulties in finding research problems, finding reference books, determining the research design, the difficulty in arranging the schedule to met the lecturer, the mismatch between the students and lecturer and the difficulties in the preparation of the scientific paper itself. This causes students to become stressed. Stress becomes more severe and bad for yourself if it can not was overcome with a good coping strategy and adaptive. The purpose of this research was to determined the relations of coping strategies with stress levels of Poltekkes Kemenkes Riau students who prepared scientific paper. This research type is quantitative research with Cross Sectional design. The research was done at Poltekkes Kemenkes Riau on 26 April - 05 May 2017. The method of sampling is total sampling by involving 71 respondents by using questionnaire for data collection. The result of statistical test obtained p value = 0,014 ( p value ≤ 0,05 ), it can be concluded that there was a significant relation between coping strategy with stress level of Poltekkes Kemenkes Riau students who made scientific paper. The more adaptive coping used in the faced of stress the lower the level of stress perceived. Therefore this research can was input for students Poltekkes Kemenkes Riau who prepared scientific paper so that they can do coping strategies for a good adjustment in the faced of stress